Content and Perspective of Students in the Professional Education Process: Konten dan Perspektif Mahasiswa dalam Proses Pendidikan Profesional - Sharipov, Abror (Pedagogia : Jurnal Pendidikan, 2025)
This study focuses on the problems of employment of the graduates from vocational education institutions in Uzbekistan and describes growing need for middle level personnel in the Uzbekistan and the international labor markets. Therefore, although educational reforms continue, gaps remain in vocational training in term of their relevance to market demands, leaving workers prone to instability in the labor market and poor employment conditions. This research uses a qualitative approach to describe government policies, international best practices, and labor market trends. Results demonstrate that through reforms are strategic, digitalizing the employment process, and stronger public-private partnerships, graduate employability can be improved. The results highlight the need for modernization of vocational training systems and further refining the dynamic labor market. Implications drawn from these insights for policymakers, educational institutions, and industry stakeholders regarding creating a sustainable employment ecosystem in the context of the Philippines and other developing economies are also provided. Highlights: Employment Challenges: Gaps in vocational training reduce job stability and employability. Strategic Reforms: Digitalization and public-private partnerships improve graduate employment. Global Relevance: Lessons from Uzbekistan apply to other developing economies like the Philippines. Keywords: Vocational Education, Labor Market, Employment, Digitalization, Workforce Development